Penerapan Lima Pilar Program Penanganan Stunting melalui Program Dapur Sehat Atasi Stunting (DAHSAT) dengan Pemanfaatan Keberlimpahan Pangan Lokal Keong Sawah - Fitria, Baiq; Wiwin Lastyana; Novia Zuriatun Sholehah; Christine Angelica (Insan Kreasi Media, 2023)
The prevalence of stunting in NTB is 35%. This community service activity aims to find solutions for problems faced by the kader of Jelantik Village in improving healh degree, by making various processed products based on local food (snails). Snails products found in Rice Field of Jelantik Village are very abundant. Kader of Jelantik village do not know how to process rice field snails into nutritious food, then it is necessary to provide snails processing skills to the community in Jelantik Village so that it is expected to increase knowledge and skills that can used to improve the health. Methods used in this activities, are: Providing training material modules to be implemented; The presentation of the material is in accordance with the contents of the recipe book plus material on food nutrition, hygiene and sanitation, kitchen management, and product packaging related to the posyandu business to be run. The output target of the activity is that participants can increase their knowledge and skills in producing various snails; participants are able to organize and manage the posyandu business properly and sustainably; the presence of a variety of local food-based specialty preparations which can be used as PMT for toddlers.